2019
DOI: 10.1109/lwc.2019.2899599
|View full text |Cite
|
Sign up to set email alerts
|

On-Demand Density-Aware UAV Base Station 3D Placement for Arbitrarily Distributed Users With Guaranteed Data Rates

Abstract: In this letter, we study the on-demand UAV-BS placement problem for arbitrarily distributed users. This UAV-BS placement problem is modeled as a knapsack-like problem, which is NP-complete. We propose a density-aware placement algorithm to maximize the number of covered users subject to the constraint of the minimum required data rates per user. Simulations are conducted to evaluate the performance of the proposed algorithm in a real environment with different user densities. Our numerical results indicate tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
68
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(75 citation statements)
references
References 8 publications
0
68
0
Order By: Relevance
“…The feasibility of supporting UAVs with existing cellular infrastructure is also studied by researchers, where it is concluded that the interference can be minimized by careful design of network parameters to satisfy the quality of service (QoS) requirements [25]. The density-aware UAV placement is studied in [26] for distributed users such that the number of users served by the UAV-based base station is maximized under the given minimum rate requirement per user. Spectrum is another focus area for cellular connected UAVs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The feasibility of supporting UAVs with existing cellular infrastructure is also studied by researchers, where it is concluded that the interference can be minimized by careful design of network parameters to satisfy the quality of service (QoS) requirements [25]. The density-aware UAV placement is studied in [26] for distributed users such that the number of users served by the UAV-based base station is maximized under the given minimum rate requirement per user. Spectrum is another focus area for cellular connected UAVs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lyu et al [9] investigated the UAV-BS placement problem, and the objective is to minimize the number of required DBSs while each UE is at least covered by one DBS. Lai et al [10] investigated the UAV-BS placement problem in a hot spot area and the goal is to maximize the number of covered UEs under given data rate requirements. Mei et al [11] proposed to utilize cooperative beamforming to alleviate the downlink interference as the DBS reuses the frequency spectra already assigned to the ground BSs, and the target is to maximize the received SINR in the DBS.…”
Section: Introductionmentioning
confidence: 99%
“…Recent study [2] on UAV-BSs mainly focuses on finding the optimal placement of the UAV-BSs while serving the user equipments (UEs) in the target area. However, in most papers [3] [4] [5], few take dynamic scenarios into consideration. In real scenarios, the UAV-BSs are expected to dynamically reposition in response to the dynamic movement of UEs.…”
Section: Introductionmentioning
confidence: 99%
“…1) In the initial time slot, cluster the UEs by using the Kmeans algorithm, and divide UEs into n clusters. 2) Use the density-aware placement algorithm[5] to find the local optimal positions of each cluster to deploy UAV-BSs in the initial time slot. Let the UAV-BSs fly to those positions.…”
mentioning
confidence: 99%